Effect of DEM and Gravity Field Representation Strategy On Regional Gravity and Height Anomaly Recovery By the Spectral Enhancement Method - Miao Lin; Song Cheng; Minjia Liu; Yuming Shi; Jianjun Zhu (Studia Geophysica et Geodaetica, 2026)

Mycorrhizal associations influence the origin and stability of topsoil organic carbon fractions: implications for subtropical forest restoration - Yongmeng Jiang; Maokui Lyu; Haohao Su; Yuming Lu; Cui Deng; Jueling Liu; Man Wang; Weisheng Lin; Jinsheng Xie (Forest Ecology and Management, 2026)

Hierarchical core–shell nanoplatforms based on sacrificial template-directed ZnO2@ZIF-8 for spatiotemporally controlled and self-augmented chemodynamic–photothermal antibacterial therapy - Yi-Fei Hui; Duan-Ping Hu; Yi Zhao; Shulin Li; Zhi-Feng Cai; Lin-Yi Li; Yuming Xie; Yong-Nian Zeng; Zu-Jin Lin; Fa-Qiang Tang (Chemical Engineering Journal, 2026)

Load response of a 15 MW floating offshore wind turbine under wind-wave conditions using a fully coupled free-wake vortex model - Zedong Wang; Chusen Lin; Songtao Wang; Yuming Yuan; Hengming Zhang; Binzhen Zhou; Zhiqiang Hu; Yan Chen (Ocean Engineering, 2026)

A simple model for localized blockage effects in multi-rotor wind turbines derived from numerical simulations - Yuming Yuan; Zhiwei Yang; Yao Luo; Chaonuan Lin; Zuli Nie; Guiyu Cao; Xiaowei Deng; Binzhen Zhou (Ocean Engineering, 2026)

Functional complementarity of abundant and rare taxa mediates soil carbon sequestration during subtropical forest restoration - Yuming Lu; Maokui Lyu; Yongmeng Jiang; Cui Deng; Jueling Liu; Man Wang; Weisheng Lin; Jinsheng Xie (Journal of Environmental Management, 2026)

Transportation carbon emission prediction based on improved long and short-term memory deep learning from the perspective of carbon emission efficiency - Lin Liu; Yuming Liu; Rong Zhao; Xizhen Xu (Environment, Development and Sustainability, 2026)

Hydrodynamic Performance Assessment of a Hybrid Wave Energy Converter Array–Floating Breakwater System Under Irregular Waves - Hengming Zhang; Chusen Lin; Chengrong Wang; Xu Huang; Yifeng Yang; Binzhen Zhou; Yingyi Liu; Yuming Yuan (Journal of Marine Science and Engineering, 2026)
A hybrid system combining wave energy converters (WECs) and a floating breakwater presents significant potential for developing commercial-scale wave power operations. The assessment of the hydrodynamic characteristics of a WEC array–floating breakwater system under irregular waves remains in the early stages and requires further investigation. Based on the linear potential theory, a time-domain numerical model is established to evaluate the performance of a hybrid WEC array–floating breakwater system in a target sea area. The interaction between the WECs and the floating breakwater is analyzed. Results show that for the hybrid system with a triangular-baffle-type WEC array under irregular waves, the annual average wave power is 1.16 MW and the annual energy production is 10.16 × 103 MW·h, representing a 241.2% improvement compared with that of the isolated WEC array. The standard deviations of the mooring forces for the hybrid system with the triangular-baffle-type WEC array are reduced by 13.8% in the surge direction and 26.9% in the pitch direction, while increasing by 90.0% in the heave direction. Similar conclusions are obtained for the motion of the floating breakwater. The findings and data reported in this study provide guidance for the engineering application of a hybrid WEC array–floating breakwater system.

Interplay of habitat heterogeneity and sampling gear in structuring nekton communities: Insights from niche overlap and biomass spectra in a mangrove estuary - Yuming Wang; Xinyi Gao; Jiakang Liu; Yutong Ma; Miaozhi Lin; Tuohui Ye; Jianxiang Feng (Continental Shelf Research, 2026)

Wave attenuation and energy conversion of a twin-parabolic floating breakwater and cylindrical heaving WEC hybrid system - Binzhen Zhou; Chaonuan Lin; Zhi Zheng; Yifeng Yang; Peng Jin; Nan Hu; Yuming Yuan (Ocean Engineering, 2026)

Endogenous formation of Fe-bearing particles and their differentiation from exogenous exposure - Yuming Huang; Lin Liu; Hang Yang; Huixuan Yi; Xiangyu Li; Linqian Li; Dawei Lu; Qian Liu; Guibin Jiang (Journal of Environmental Sciences, 2025)

Ethylene-responsive factor HvERF72 regulates starch synthesis and B-type starch granules initiation in barley - Gaozong Zhou; Jinjin Ding; Yulong Li; Qiang Xu; Yazhou Zhang; Huaping Tang; Pengfei Qi; Mei Deng; Jian Ma; Guoyue Chen; Jirui Wang; Na Lin; et al. (Carbohydrate Polymers, 2025)

Co-encapsulation of an AKT Inhibitor Enhances the Tumor-cell Selectivity of STING Agonists in Co-delivery Liposomes - Ziyu Ge; Qiang Zhang; Yuming Wang; Lin Miao; Xinqi Wang; Ni Fan; LiLi Duan; Yunfei Li; Xue-Jie Qi (Pharmaceutical Research, 2025)

The nexus of digital economy and regional green innovation: the moderating roles of formal and informal institutions - Yuming Zhai; Ning Xie; Han Lin; Linguo Ji; Mingchuan Yu (Environment, Development and Sustainability, 2025)

Numerical Analysis of Thermal–Structural Coupling for Subsea Dual-Channel Connector - Feihong Yun; Yuming Du; Dong Liu; Xiaofei Wu; Minggang Tang; Qiuying Yan; Peng Gao; Yu Chen; Xu Zhai; Hanyu Sun; Songlin Zhang; Shuqi Lin; et al. (Journal of Marine Science and Engineering, 2025)
In deep-sea oil and gas development scenarios, deep-sea dual-channel connectors often face the risk of seal failure due to internal and external temperature difference loads. To address this issue, this paper systematically establishes equivalent heat transfer models for the key parts of the connector based on the third-type boundary condition. On this basis, the quantitative correlation between the equivalent thermal conductivity, composite heat transfer coefficient and temperature of each part is explored. Using the finite element numerical simulation method, the transient temperature field of the connector under three working conditions (heating, cooling and temperature shock) is simulated and analyzed, revealing the temperature distribution characteristics and temperature change trends of the maximum temperature difference of each key component of the connector; combined with thermal–structural coupling simulation, the temperature field is converted into static load, to determine the behavior of the contact stress on the sealing surface under different temperature–pressure coupling working conditions; in addition, by placing the test prototype in a high-low temperature cycle chamber, the seal performance tests under pressurized and non-pressurized working conditions are carried out to verify the reliable sealing performance of the connector under variable temperature conditions. The results of this paper provide comprehensive theoretical support and an experimental basis for the thermodynamic optimization design of deep-sea connectors and the improvement of the reliability of the sealing system.

Leveraging LLM-based multi-agent simulations to boost participatory design education: An experimental exploration in residential area design - Yudi Zhang; Yuming Lin; Li Tian; Xin Yang (Sustainable Cities and Society, 2025)

Numerical simulation and performance analysis of in-field blockage effect between wind turbines - Binzhen Zhou; Chaonuan Lin; Zhiwei Yang; Zuli Nie; Yuming Yuan; Peng Jin (Ocean Engineering, 2025)

Dual-function activity prediction of fingered citron: Integrating hypotensive and Hypolipidaemic effects via molecular docking and QSAR methods - Yuming Zhong; Ningjing Zhou; Huifan Liu; Bingting Lu; Huang Peng; Jialin Chen; Canhuan Liang; Lin Zhang (Food Chemistry, 2025)

Resveratrol-integrated Se-chitosan nanogel for protein corona-mediated blood-brain barrier traversing and anti-inflammatory treatment for Parkinson's disease - Yuan Cao; Linwei Zhao; Qing Li; Bo Song; Yuming Xu; Lin Jiang; Shaohua Li (Chemical Engineering Journal, 2025)

In vitro and in vivo evidence on the association of pregnant PM2.5 exposure with preterm birth and potential role of placental miRNA-21 regulating TLR4/NF-κB and activating NLRP3 inflammasome - Shanshan Ran; Wenxue Li; Zijun Yang; Jingyi Zhang; Zhangjian Chen; Guang Jia; Qingmei Lin; Huai-cai Zeng; Yin Yang; Zilong Zhang; Yonggui Gao; Lan Chen; et al. (Journal of Hazardous Materials, 2025)

Hydrodynamic performance and narrow gap resonance of WEC-floating breakwater hybrid system: An experimental study - Binzhen Zhou; Chusen Lin; Xu Huang; Qi Zhang; Yuan Yuming; Hengming Zhang; Peng Jin; Yifeng Yang (Ocean Engineering, 2025)

Deflection influence line - based bridge damage detection using high-resolution modal flexibility matrix with limited sensors - Yuming Lin; Zimo Zhu; Hongwei Ma; Zhenhua Nie (Engineering Structures, 2025)

Unveiling Leydig cell heterogeneity and its role in male infertility: A single-cell transcriptomic study of human testicular tissue - Liwei Zhou; Hanchao Liu; Yuming Chen; Lin Hua; Xiaolong Wu; Xintao Gao; Le Mao (Reproductive Biology, 2025)

Successful oral RNA interference efficiency in the silkworm Bombyx mori through nanoparticle-shielded dsRNA delivery - Jisheng Liu; Yang Yang; Qiangjun Yang; Xianfeng Lin; Yuming Liu; Ziyang Li; Luc Swevers (Journal of Insect Physiology, 2025)

Harnessing multi-target nanosweepers inhibiting β-amyloid aggregation, scavenging reactive oxygen species and overcoming the blood brain barrier for rescuing Alzheimer’s disease - Yixuan Wang; Chaoren Yan; Yuming Qi; Ruobing Zhao; Yan Wan; Zhaoyuan Lyu; Yansong Li; Zhijuan Wang; Changqing Li; Yuehe Lin; Qian Chen; Shichao Ding; et al. (Chemical Engineering Journal, 2025)

Modeling flood and breach evolution of the landslide dam due to overtopping - Fei Zhang; Shilin Jia; Xingbo Zhou; Lin Wang; Yuming Zhu (Journal of Hydrology, 2025)

Temperature-responsive gating chitosan-based microcapsules for controlled release of urea fertilizers - Nian Xiang; Yuming Lin; Zuzeng Qin; Tongming Su; Xinling Xie; Hongbing Ji (Carbohydrate Polymers, 2025)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Bavachinin, a main compound of Psoraleae Fructus, facilitates GSDMD-mediated pyroptosis and causes hepatotoxicity in mice - Wei Shi; Yuan Gao; Huijie Yang; Hui Li; Tingting Liu; Jia Zhao; Ziying Wei; Li lin; Yujiao Huang; Yuming Guo; Anlong Xu; Zhaofang Bai; et al. (Chemico-Biological Interactions, 2024)

Ambient air pollution, lifestyle, and genetic predisposition on all-cause and cause-specific mortality: A prospective cohort study - Yiqun Zhu; Yao Wu; Jun Cheng; Huaying Liang; Qinyu Chang; Fengyu Lin; Dianwu Li; Xin Zhou; Xiang Chen; Pinhua Pan; Hong Liu; Yuming Guo; et al. (Science of The Total Environment, 2024)

Long-term exposure to ambient ozone and adult-onset asthma: A prospective cohort study - Jiayue Zhang; Baozhuo Ai; Yuming Guo; Lan Chen; Ge Chen; Haitao Li; Hualiang Lin; Zilong Zhang (Environmental Research, 2024)

Three-phase Enriched Environment Improves Post-stroke Gait Dysfunction via Facilitating Neuronal Plasticity in the Bilateral Sensorimotor Cortex: A Multimodal MRI/PET Analysis in Rats - Yun Lu; Ziyue Lin; Mingcong Li; Yuming Zhuang; Binbin Nie; Jianfeng Lei; Yuanyuan Zhao; Hui Zhao (Neuroscience Bulletin, 2024)

Source-Specific Ecological Risk of Atmospheric PM2.5-Bound Metals and Implications for Air Pollution Control: A Regional Perspective from China - Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Qiannan Wei; Shaojie Fu; Dejian Mai; Luan Yuan; Qing Wei; Dingli Yue; Qiansheng Hu (Exposure and Health, 2024)

Causal association between long-term exposure to air pollution and incident Parkinson’s disease - Baozhuo Ai; Jiayue Zhang; Shiyu Zhang; Ge Chen; Fei Tian; Lan Chen; Haitao Li; Yuming Guo; Angela Jerath; Hualiang Lin; Zilong Zhang (Journal of Hazardous Materials, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Considering biotic interactions exacerbates the predicted impacts of climate change on coral‐dwelling species - Zhixin Zhang; Shaobo Ma; Ákos Bede‐Fazekas; Stefano Mammola; Meng Qu; Jinxin Zhou; Ellias Yuming Feng; Geng Qin; Qiang Lin (Journal of Biogeography, 2024)
Aim Climate change is affecting the geographic distributions of many species and researchers are increasingly relying on species distribution models (SDMs) to forecast species' redistributions under climate change. Such modelling studies, however, often ignore biotic interactions that shape species' geographic ranges. This is especially problematic for coral reefs, which host a high diversity of species and interactions. We tested how biotic interactions affect the distribution patterns of obligate coral‐dwelling Trapezia crabs. Location Global coastal ocean. Time Period 2000–2014, 2040–2050, 2090–2100. Major Taxa Studied Corals and coral‐dwelling Trapezia crabs. Methods We determined the symbiotic relationships between 22 crab species in the genus Trapezia and corals via field survey and extensive literature review. We first developed SDMs for coral and crab species using exclusively abiotic variables (abiotic‐only models for corals and crabs). Then we constructed a second set of models where we accounted for coral distributions into crab predictions by combining model predictions for the two taxa a posteriori (abiotic‐plus‐biotic models for crabs only). Results We obtained 30 commonly accepted coral‐crab symbiotic relationships from nine Trapezia crab and six stony coral species. The abiotic‐only model predictions showed that six corals may lose approximately one‐sixth of suitable ranges under RCP 8.5 in 2040–2050. The two types of models for crabs yielded largely different habitat suitability predictions and accounting for biotic interactions into SDM predictions exacerbates the predicted impacts of climate change on coral‐dwelling crabs. Main Conclusions Our results show large discrepancies in crab spatial distribution patterns with and without accounting for symbiotic interactions. Our findings highlight the important role of modeller's decision on accounting for biotic interactions when predicting the geographical ranges of coral‐dwelling species, with important implications for designing future conservation and management strategies for marine species.

Seismic performance of prefabricated wall panels with sliding joints for reinforced concrete frames - Chao Zhang; Zijian Lin; Tianhao Yu; Weiyuan Huang; Xuesong Deng; Zexin Lin; Yuming Huang (Bulletin of Earthquake Engineering, 2024)

Construction land reduction projects as a pathway to sustainability: an empirical analysis of risks factors in China - Bingxu Mu; Yuming Zhu; Naveed Ahmad; Jiahe Zhou; Lei He; Hongli Lin (Environmental Science and Pollution Research, 2024)

Role of antenatal anxiety in the relationship between maternal exposure to nitrogen dioxide and small for gestational age: A birth cohort study - Qiannan Wei; Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Zhenyan Han; Qingqing Wang; Lijie Wang; Wenzhuo Li; Li Wen; Hongying Hou; Qiansheng Hu (Science of The Total Environment, 2023)

The effects of prenatal PM2.5 oxidative potential exposure on feto-placental vascular resistance and fetal weight: A repeated-measures study - Weiwei Lin; Yuming Lai; Shuling Zhuang; Qiannan Wei; Hedi Zhang; Qiansheng Hu; Peng Cheng; Manman Zhang; Yuhong Zhai; Qingqing Wang; Zhenyan Han; Hongying Hou (Environmental Research, 2023)

Breaking the dilemma of low selectivity in the oxidative coupling of methane over Mn-Na2WO4/SiO2 at low temperatures - Lin Xu; Anna Zanina; Kai Wu; Jianshu Li; Juan Chen; Yuming Li; Guiyuan Jiang; Evgenii V. Kondratenko (Chemical Engineering Journal, 2023)

Quantitative proteomics provides insights into the mechanism of the differences in heat-induced gel properties for egg white proteins with different interior quality during ageing in laying hens - Guang Li; Siyuan Mi; Qi Zeng; Lin Wang; Xingbo Liu; Ming Zhang; Zengpeng Lv; Yongguo Jin; Junyou Li; Yuming Guo; Bingkun Zhang (Food Chemistry, 2023)

The ionome and proteome landscape of aging in laying hens and relation to egg white quality - Guang Li; Yuqing Feng; Jian Cui; Qihang Hou; Tanfang Li; Meiting Jia; Zhengtian Lv; Qiuyu Jiang; Ying Wang; Ming Zhang; Lin Wang; Zengpeng Lv; et al. (Science China Life Sciences, 2023)

Microbiological mechanism for “production while remediating” in Cd-contaminated paddy fields: A field experiment - Jiguang Gu; Fang Guo; Lihong Lin; Jiexiang Zhang; Weimin Sun; Riaz Muhammad; Haojie Liang; Dengle Duan; Xingying Deng; Zheng Lin; Yifan Wang; Yuming Zhong; et al. (Science of The Total Environment, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Understanding stakeholder relationships in sustainable brownfield regeneration: a combined FAHP and SNA approach - Hongli Lin; Yuming Zhu; Jiahe Zhou; Bingxu Mu; Caihong Liu (Environment, Development and Sustainability, 2023)

A high-efficient anisotropic continuum model for the optimization of heat transfer and chemical reaction in a packed-bed water gas shift reactor - Bo Jiang; Haonan Wang; Kewei Yu; Jing Ma; Wang Si-ma; Yuming Gao; Lin Li; Xinwei Zhang; Huiru Cui; Dawei Tang (Fuel, 2023)

A novel all-natural (collagen+pectin)/chitosan aqueous two-phase microcapsule with improved anthocyanin loading capacity - Zhenyang Jiang; Shaojie Zhao; Zhiying Fan; Chengying Zhao; Lin Zhang; Dan Liu; Yuming Bao; Jinkai Zheng (Food Hydrocolloids, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Comparison of groundwater hydrogeochemistry of karst areas in northern and southern China with emphasis on their performance in karst development - Peng Yuming; Xiao Qiong; Xue Honglei; Lv Minghui; Lin Guangqi; Zhao Haijuan; Wu Peiyan; Guo Yongli (Carbonates and Evaporites, 2022)

Characterization and fine mapping of a lesion mimic mutant (Lm5) with enhanced stripe rust and powdery mildew resistance in bread wheat (Triticum aestivum L.) - Cong Li; Hang Liu; Jian Wang; Qi Pan; Yue Wang; Kunyan Wu; Peiying Jia; Yang Mu; Huaping Tang; Qiang Xu; Qiantao Jiang; Yaxi Liu; et al. (Theoretical and Applied Genetics, 2022)

Analysis of the starch properties in tetraploid wheat–Aegilops sharonensis amphidiploid - Qing Li; Xuteng Zhang; Na Lin; Guzmán Carlos; Jingyu Lan; Huaping Tang; Pengfei Qi; Jian Ma; Jirui Wang; Guoyue Chen; Wei Li; Zhien Pu; et al. (Cereal Research Communications, 2021)

A Comparative Study About the Neuroprotective Effects of EPA-Enriched Phosphoethanolamine Plasmalogen and Phosphatidylethanolamine Against Oxidative Damage in Primary Hippocampal Neurons - Yunfang Zhu; Tiantian Zhang; Lin Ding; Haohao Shi; Changhu Xue; Wancui Xie; Hongxia Che; Yuming Wang (Journal of Ocean University of China, 2021)

Identification and validation of stable quantitative trait loci for grain filling rate in common wheat (Triticum aestivum L.) - Yu Lin; Xiaojun Jiang; Yang Tao; Xilan Yang; Zhiqiang Wang; Fangkun Wu; Shihang Liu; Caixia Li; Mei Deng; Jian Ma; Guangdeng Chen; Yuming Wei; et al. (Theoretical and Applied Genetics, 2020)

Stakeholders’ perspective on strategies to promote contaminated site remediation and brownfield redevelopment in developing countries: empirical evidence from Pakistan - Naveed Ahmad; Yuming Zhu; Jing Shao; Hongli Lin (Environmental Science and Pollution Research, 2020)

Age Matters: an Atypical Association Between Polymorphism of MTHFR and Clinical Phenotypes in Children with Schizophrenia - Lin Wan; Yuhong Li; Yuming Zhou; Rena Li; Yi Zheng (Journal of Molecular Neuroscience, 2019)

Molecular cloning of the cpeT gene encoding a bilin lyase responsible for attachment of phycoerythrobilin to Cys-158 on the β-subunit of phycoerythrin in Gracilariopsis lemaneiformis - Xuexue Cao; Xiaonan Zang; Zhu Liu; Yuming Jin; Deguang Sun; Yalin Guo; Zhendong Wang; Feng Zhang; Jiaojiao Lin (Journal of Applied Phycology, 2019)

A breeding strategy targeting the secondary gene pool of bread wheat: introgression from a synthetic hexaploid wheat - Ming Hao; Lianquan Zhang; Laibin Zhao; Shoufen Dai; Aili Li; Wuyun Yang; Die Xie; Qingcheng Li; Shunzong Ning; Zehong Yan; Bihua Wu; Xiujin Lan; et al. (Theoretical and Applied Genetics, 2019)

Quantitative trait locus mapping for panicle exsertion length in common wheat using two related recombinant inbred line populations - Yang Tao; Xin Yi; Yu Lin; Zhiqiang Wang; Fangkun Wu; Xiaojun Jiang; Shihang Liu; Mei Deng; Jian Ma; Guangdeng Chen; Yuming Wei; Youliang Zheng; et al. (Euphytica, 2019)

A scientometric analysis and visualization of global research on brownfields - Hongli Lin; Yuming Zhu; Naveed Ahmad; Qingye Han (Environmental Science and Pollution Research, 2019)

Identification and validation of a novel major QTL for all-stage stripe rust resistance on 1BL in the winter wheat line 20828 - Jian Ma; Nana Qin; Ben Cai; Guoyue Chen; Puyang Ding; Han Zhang; Congcong Yang; Lin Huang; Yang Mu; Huaping Tang; Yaxi Liu; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Cloning of ho gene from Gracilariopsis lemaneiformis and study on its function on the synthesis of a fluorescent phycoerythrobilin in heterologous hosts - Yuming Jin; Xiaonan Zang; Xiaoyun Huang; Xuexue Cao; Deguang Sun; Jiaojiao Lin; Zhu Liu; Chang Liu; Yalin Guo; Zhendong Wang; Lulu Hou (Journal of Applied Phycology, 2018)

FGF21 Attenuates High-Fat Diet-Induced Cognitive Impairment via Metabolic Regulation and Anti-inflammation of Obese Mice - Qingzhi Wang; Jing Yuan; Zhanyang Yu; Li Lin; Yinghua Jiang; Zeyuan Cao; Pengwei Zhuang; Michael J. Whalen; Bo Song; Xiao-Jie Wang; Xiaokun Li; Eng H. Lo; et al. (Molecular Neurobiology, 2018)

Identification and validation of novel low-tiller number QTL in common wheat - Zhiqiang Wang; Yaxi Liu; Haoran Shi; Hongjun Mo; Fangkun Wu; Yu Lin; Shang Gao; Jirui Wang; Yuming Wei; Chunji Liu; Youliang Zheng (Theoretical and Applied Genetics, 2016)

Cyclin D1 polymorphism and oral cancer: a meta-analysis - Wenjun Wang; Yuming Zhao; Jie Yang; Bichen Lin; Haiyong Gu; Xiaoqing Cao; Lihong Ge (Molecular Biology Reports, 2013)